Intensified conditioning regimen with fludarabine combined with post-transplantation cyclophosphamide for haploidentical allogeneic hematopoietic stem cell transplantation in children with high-risk acute leukemia - Junjie Cao; Xiaodong Xu; Ying Lu; Tiantian Wang; Dong Chen; Shuangyue Li; Xuhui Liu; Peipei Ye; Zhong-zheng Zheng; Renzhi Pei (Hematology, 2023)
ABSTRACTObjective: Post-transplantation cyclophosphamide (PTCy) can reduce the incidence of graft versus host disease (GVHD) and this intervention is often applied on adults with hematologic malignancy. However, the high relapse rate hinders the development of the intervention and data of PTCy used on children with hematologic malignancy remains limited. In order to overcome issue of high relapse rate in PTCy treatment, we used fludarabine (Flu), enhanced dose of cytarabine (Ara-C, 9 g/m2), busulfan (Bu), Cy, anti-thymocyte globulin (ATG) combined with PTCy for an intensified conditioning regimen.Methods: A total of 22 children with acute leukemia received intensified PTCy conditioning regimen (PTCy intensified group). We matched with 18 children who received modified Bu-Cy and ATG conditioning regimen in the same period (ATG group).Results: The two-year cumulative incidences of grade II–IV acute GVHD was significantly lower in PTCy intensified group (13.6 ± 7.7% vs 38.9 ± 11.5%, P = 0.048). Two-year GVHD-free relapse free survival (GRFS) in PTCy seems to be better among the increment group despite not being significant (63.3 ± 10.3% vs 35.4 ± 11.9%, P = 0.092). The positive rate of minimal residual disease after transplantation was significantly lower than that before transplantation (20.0% vs 2.5%, P = 0.029).Conclusion: In conclusion, ATG and PTCy combined with Flu-based increased intensity conditioning regimen is effective for acute leukemia in children. It could reduce GVHD rate significantly and potentially improve GRFS.